2002
DOI: 10.1128/aac.46.7.2234-2237.2002
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Triazoles and Polymorphonuclear Leukocytes Synergize To Cause Increased Hyphal Damage toScedosporium prolificansandScedosporium apiospermum

Abstract: Scedosporium prolificans and Scedosporium apiospermum (Pseudallescheria boydii) cause pulmonary and disseminated infections refractory to most currently used antifungal agents in immunocompromised patients. We therefore investigated the potential antifungal activities of the triazoles itraconazole (ITC), voriconazole (VRC), and posaconazole (PSC) in combination with human polymorphonuclear leukocytes (PMNs) against the hyphae of these fungal pathogens. A colorimetric assay with (2,3-bis[2-methoxy-4-nitro-5-sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Of note, the synergistic activity has been observed at low concentrations of the antifungals. This finding may be of particular importance, especially in immunocompromised patients, when a triazole reaches its trough level in plasma where such synergy may prevent fungal regrowth (152). Regardless of the mechanisms behind these collaborative effects, the findings from these studies would support the concomitant administration of antifungals and PMN transfusions to persistently neutropenic patients with invasive scedosporiosis.…”
Section: Immunotherapymentioning
confidence: 79%
See 1 more Smart Citation
“…Of note, the synergistic activity has been observed at low concentrations of the antifungals. This finding may be of particular importance, especially in immunocompromised patients, when a triazole reaches its trough level in plasma where such synergy may prevent fungal regrowth (152). Regardless of the mechanisms behind these collaborative effects, the findings from these studies would support the concomitant administration of antifungals and PMN transfusions to persistently neutropenic patients with invasive scedosporiosis.…”
Section: Immunotherapymentioning
confidence: 79%
“…Triazoles (itraconazole, voriconazole, and posaconazole) have additive antifungal activities in combination with PMNs against S. apiospermum. Voriconazole plus posaconazole demonstrated synergistic interactions with PMNs against S. prolificans (152). In a murine model of Scedosporium infection, Ortoneda and colleagues (325) demonstrated that liposomal amphotericin B plus G-CSF improved survival over that with liposomal amphotericin B or amphotericin B deoxycholate.…”
Section: Immunotherapymentioning
confidence: 99%
“…These studies suggested that immunomodulators may be acting via neutrophils (Th1 response) or monocytes (inducing tumor necrosis factor and macrophage inflammatory protein 1␣). In separate studies, VORI, POSA, and ITRA enhanced the antifungal functions of human PMNs against hyphae of S. prolificans and S. apiospermium (81). Similarly, AmB lipid complex plus PMN displayed a significant additive effect against both Scedosporium species (22% for S. prolificans and 81% for S. apiospermum; P Ͻ 0.04) (80).…”
Section: Antifungals Combined With Immunomodulatorsmentioning
confidence: 87%
“…Importantly, antagonism was not observed with any of these combinations. Gil-Lamaignere et al showed a synergistic effect of voriconazole or posaconazole with neutrophils in vitro against hyphae of S. prolificans (285). Older literature also suggests synergy with ketoconazole and 5-FC for a variety of dematiaceous fungi (152).…”
Section: Antifungal Combinationsmentioning
confidence: 99%